THE MEDIATING ROLE OF BRAND EXPERIENCE IN SOCIAL MEDIA MARKETING’S IMPACT ON BRAND EQUITY AND PURCHASE INTENTION - Gultom , Sarah Bunga Dili Oktavia; Munandar, Jono M; Purwono, Joko (LPPM Universitas Jambi, 2026)
The rapid growth of social media has transformed marketing strategies in the restaurant industry. Despite this, limited research has examined the integration of social media marketing activities (SMMA), brand experience, and purchase intention within the Indonesian restaurant context. This study aims to investigate the influence of SMMA on brand equity and purchase intention, with brand experience serving as a mediating variable. A quantitative survey was conducted among 310 Instagram followers of Medja Restaurant. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 22 to test the relationships among SMMA, brand experience, brand equity, and purchase intention. Findings indicate that SMMA positively impacts both brand experience and brand equity. Brand equity significantly predicts purchase intention, while brand experience partially mediates the relationship between SMMA and brand equity. The results suggest that restaurant managers should develop interactive, personalized, and emotionally engaging social media content to enhance customer experience, strengthen brand equity, and increase purchase intentions. This study is the first to integrate SMMA, brand experience, and purchase intention into a single SEM framework in the Indonesian restaurant industry, providing empirical evidence for the mediating role of brand experience.